MODERN METHODS OF INCREASING THE EFFICIENCY OF BANK ASSETS (Marketing Journal, 2025)
This article analyzes the traditional and modern methods for improving the efficiency of bank assets in the Republic of Uzbekistan and explores opportunities to accelerate the activities of commercial banks through the development of this area. Special att ention is given to the measures implemented during the consistent reform of the financial sector, the introduction of advanced banking practices, and the establishment of legal conditions aimed at strengthening competition within the sector. Furthermore, t he study identifies current challenges in enhancing bank asset efficiency and presents the authorʼs approaches and practical recommendations for addressing these issues. 322
Keywords: commercial bank; digital transformation; innovative bank; banking products; management structure; bank strategy; assets; bank assets; bank liabilities; margin; credit; deposit; interest income; non -interest income; expenses